Influence of chomper chums application towards private elementary school student’s PHP index : Study experimental - Abigayl, Ivana; Timothy, Sampurna Kevin; Apriani, Anie; Monica, Grace; Dinata, Surya (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Oral health is essential to a child’s overall well-being. Poor oral hygiene can result in dental caries, discomfort, and negatively affect daily functions such as eating, speaking, and learning. Traditional education methods like lectures often fail to engage children effectively. This study aims to analyze  the impact of Chomper Chums, a gamified mobile health application, on improving oral hygiene among elementary students at SDK Yahya Bandung. Methods: This study was a randomized controlled trial involving 175 students from grades I–VI at SDK Yahya Bandung. Samples were obtained using a total sampling technique and randomly assigned to intervention and control groups. Oral hygiene was assessed using the Personal Hygiene Performance (PHP) index with Triplaque ID gel. Data analysis was performed using SPSS version 27, employing descriptive and inferential statistical tests, including the Chi-square test, Mann–Whitney test, Spearman correlation, and simple linear regression Results: The study was divided into a control group that received health education (n = 87) and an intervention group that used an application (n = 88), with participants aged 7–12 years. The highest frequency distribution was observed in the 10- and 11-year age groups, each comprising 37 students. The results showed that before the intervention there was no significant difference in the Personal Hygiene Performance (PHP) index between the intervention and control groups (p>0.05). After the intervention, the reduction in PHP index in the Chomper Chums application group was significantly greater than in the counseling group (p<0.001). This indicates that the Chomper Chums application is more effective in improving students’ oral hygiene.Conclusion: Chomper Chums demonstrates strong potential as an effective, child-friendly oral health education tool. Further research is recommended for long-term impact evaluation.KEYWORDS: oral hygiene, dental health education, mobile applications, gamification, dental plaque index, randomized controlled trialPengaruh aplikasi chomper chums terhadap indeks PHP siswa sekolah dasar swasta: Studi eksperimentalABSTRAKPendahuluan: Kesehatan gigi dan mulut berperan penting dalam kesejahteraan anak. Kebersihan gigi yang buruk dapat menyebabkan karies, ketidaknyamanan, serta mengganggu aktivitas seperti makan dan belajar. Edukasi tradisional sering kurang menarik bagi anak-anak, sehingga pendekatan inovatif seperti aplikasi digital mulai dikembangkan. Penelitian ini bertujuan menganalisis pengaruh aplikasi edukatif Chomper Chums terhadap kebersihan gigi anak di SDK Yahya Bandung. Metode: Penelitian ini merupakan randomized controlled trial pada 175 siswa kelas I–VI SDK Yahya Bandung. Sampel diambil dengan teknik total sampling dan dibagi secara acak menjadi kelompok intervensi dan kontrol. Kebersihan gigi diukur menggunakan indeks Personal Hygiene Performance (PHP) dengan gel Tri Plaque ID.  Analisis data dilakukan menggunakan SPSS 27 dengan uji deskriptif dan inferensial, meliputi uji Chi-Square, Mann-Whitney, korelasi Spearman, serta regresi linier sederhana Hasil: Penelitian dibagi menjadi kelompok kontrol yang menerima penyuluhan (n=87) dan kelompok intervensi yang menggunakan aplikasi (n=88), dengan rentang usia 7-12 tahun, distribusi frekuensi tertinggi terdapat pada kelompok usia 10 dan 11 tahun (masing-masing 37 siswa). Hasil penelitian menunjukkan bahwa sebelum intervensi tidak terdapat perbedaan bermakna indeks PHP antara kelompok intervensi dan kontrol (p>0,05). Setelah intervensi, penurunan indeks PHP pada kelompok aplikasi Chomper Chums secara signifikan lebih besar dibandingkan kelompok penyuluhan (p<0,001). Hal ini menunjukkan bahwa aplikasi Chomper Chums lebih efektif dalam meningkatkan kebersihan gigi dan mulut siswa. Simpulan: Chomper Chums efektif sebagai media edukasi anak dan diperlukan penelitian lanjutan untuk melihat efek jangka panjangnya.KATA KUNCI: kebersihan mulut, edukasi kesehatan gigi, aplikasi seluler, gamifikasi, indeks plak gigi